AYURVEDIC MANAGEMENT OF PSORIASIS: A CASE STUDY - Kumar Sahoo, *Sushanta; Singh, Abhilasha; Kumari, Neha (International Journal of Ayurveda and Pharma Research, 2017)
Skin is the mirror which reflects the harmony of internal functions of body. Any change in skin colour disturbs the patient both mentally and physically. Psoriasis is an autoimmune disease in which scaling and itching in the papulosquamous lesion of skin disturbs the daily routine of the patients. Because of its recurrent nature the disease has remained a great problem. There is no certain cure for this disease. Modern medicine provides symptomatic relief but also has side effects in long course. The Ayurvedic diagnosis is considered as Ekakushtha which is a Vata Kapha predominant Kshudrakushtha. Here an effort was made to treat a nineteen years old male diagnosed case of Plaque Psoriasis, by combined Ayurvedic regimen. As the principle of treatment of all types of Kushtha is Sanshodhana along with Sanshamana drugs. In this study initially Vamana karma and then Virechana karma was performed. After Sanshodhana, Sanshamana drugs were given for 40 days. PASI (Psoriasis area severity index) score was taken for assessment parameter of improvement. The skin lesions of the patient was calculated by PASI score before starting the treatment was found to be 35.1 which decreased to 5.4 at the end of treatment. This case report showed that combined Ayurvedic modalities resulted in great improvement in overall condition of the patient with no recurrence since last 1 year.